2015
DOI: 10.18632/oncotarget.4288
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal control of gene expression in bone-marrow derived cells of the tumor microenvironment induced by MRI guided focused ultrasound

Abstract: The tumor microenvironment is an interesting target for anticancer therapies but modifying this compartment is challenging. Here, we demonstrate the feasibility of a gene therapy strategy that combined targeting to bone marrow-derived tumor microenvironment using genetically modified bone-marrow derived cells and control of transgene expression by local hyperthermia through a thermo-inducible promoter. Chimera were obtained by engraftment of bone marrow from transgenic mice expressing reporter genes under tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Hyperthermia in combination with the temperature-sensitive 70 kDa heat-shock protein ( HSP70 ) promoter presents a unique approach, allowing noninvasive spatiotemporal control of transgene expression. We already demonstrated in vivo, by using transgenic mice and genetically modified cells, that focused-ultrasound (FUS) combined with real-time monitoring of the local temperature distribution by phase magnetic resonance imaging allows for a fine control of temperature increase and thus a good spatiotemporal control of local transgene expression by using thermosensitive promoters [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia in combination with the temperature-sensitive 70 kDa heat-shock protein ( HSP70 ) promoter presents a unique approach, allowing noninvasive spatiotemporal control of transgene expression. We already demonstrated in vivo, by using transgenic mice and genetically modified cells, that focused-ultrasound (FUS) combined with real-time monitoring of the local temperature distribution by phase magnetic resonance imaging allows for a fine control of temperature increase and thus a good spatiotemporal control of local transgene expression by using thermosensitive promoters [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, for this method, the activation of the Hsp70B promoter in vivo was accomplished using a water-bath which conferred the advantage of being a simple and low-cost system to induce hyperthermia on the entire tumor. More clinically relevant heating sources such as focal magnetic resonance-guided high-intensity focused ultrasound 10 , 16 could be adapted to the Hsp-controlled RNAi system to reach deep tissues and to have a more precise spatial control.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Hsp70B promoter has many advantages including its low basal activity and the heat-induced expression 8 11 which could create new approaches for Hsp-controlled RNAi systems in vivo . Moreover, the efficient control of gene expression in vivo using a HSP-related promoter has been reported using encoding genes such as HSV thymidine kinase , FAS ligand and cytokine genes 9 , 12 – 14 or reporter genes for in vivo monitoring 10 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia (a procedure that increases the body or local temperature above 37 C) [73] can be applied in a well-defined volume of tissue using appropriate heating techniques. Several studies have demonstrated the feasibility a delivering a therapeutic gene product controlled in space and time and activated by a minimally invasive heating method using a HS promoter [71,74]. The development of a novel gene therapy to treat cancer cells in which therapeutic genes are activated by heat seems a logical approach because hyperthermia is currently often used in combination with chemotherapy and radiotherapy [73].…”
Section: Therapeutic Applicationsmentioning
confidence: 99%